Uncovering the Information Literacy and Communication Skills of Biology Students in The State University of Makassar - Sitti Saenab; Siti Zubaidah; Susriyati Mahanal; Sri Rahayu Lestari; Andi Irma Suryani (JURNAL NALAR PENDIDIKAN, 2022)
Today's world necessitates information literacy and communication abilities. Mastery of information literacy and communication skills has a long-term impact on students' careers, hence information literacy and communication skills should be taught from the beginning of the lecture, while students are still in first year. This study aimed to assess information literacy skills and communication skills of students in Biology department, State University of  Makassar. The population of this study was all first year students (six classes), in the academic year of 2018/2019, who took the General Biology Course. Three classes (N = 112) became samples of this research. The research instruments were rubric of information literacy skills and communication skills. Two observers were employed to examine students skill occurring in four meetings course. The study found that Biology student information literacy skills are generally in progress level. Meanwhile, the majority of the students’ communication skills are in able tier level (level 2). The results of mapping information literacy and student communication skills can be used as input for educators in designing learning.